DNA methylation patterns associated with prior tuberculosis infection in people with HIV - Joseph Baruch Baluku; Sharon Namiiro; Daphine Kigongo Zawedde; Brenda Namanda; Hakiimu Kawalya; Irene Najjingo; Waiswa Geoffrey; Nixon Niyonzima; Naghib Bogere; Edwin Nuwagira; Joshua Rhein; Nick Jones; et al. (Scientific Reports)
Abstract Mechanisms by which prior tuberculosis (TB) increases long-term risk for cancer, cardiovascular, and neurological disorders remain unclear, particularly in people with HIV (PWH). This study investigated DNA methylation (DNAm) patterns and associated pathways in PWH with and without prior TB infection. DNAm was analyzed in blood samples from 30 PWH (10 with prior latent TB infection [LTBI], 10 with previous successfully treated active TB, and 10 with no TB) using the Illumina MethylationEPIC BeadChip covering over 850,000 CpG sites. Epigenetic age was estimated, and age acceleration was calculated. Differentially methylated CpGs (dmCpGs) and regions (DMRs) were identified, and functional enrichment analyses for Gene Ontology, KEGG pathways, PANTHER database, and gene set enrichment analysis (DisGeNET, dbGaP) were performed. Statistical significance was set at a false discovery rate (FDR) of < 0.05. PWH exhibited significant epigenetic age acceleration, with a mean of 19.32 ± 10.82 years greater than chronological age. This accelerated aging was more pronounced in individuals with any prior TB infection (21.60 ± 12.03 years) compared to those without TB (17.42 ± 9.38 years). In the prior active TB vs. no TB comparison, 7461 dmCpGs were identified, corresponding to 150 DMRs (p < 0.05), with top associated genes including GRAMD1C (hypomethylation), DPP6 (hypermethylation), and HDAC4 (hypomethylation). In the LTBI vs. no TB comparison, 8598 dmCpGs were observed, corresponding to 39 DMRs (p < 0.05), associated with genes such as PLEKHG5 (hypermethylation), STK32C (hypermethylation), and SPATC1L. When comparing any prior TB (active or latent) to no TB, 71,774 dmCpGs and 14 DMRs were identified, including genes like PLEKHG5, KCNN3, and BRSK2. Pathway analyses of prior TB (active or latent) vs. no TB revealed enrichment in neurogenesis, neuron differentiation, axon guidance, and neuroactive ligand signaling. Additional enriched pathways included those related to platelet activation, vascular muscle contraction, and chemokine signaling. Cancer-related pathways such as proteoglycans in cancer, small cell lung cancer, prostate cancer, breast cancer, hepatocellular carcinoma, and thyroid cancer were also enriched. PANTHER analysis showed consistent enrichment in the Wnt signaling pathway and inflammation-mediated pathways across compared groups. DisGeNET analysis linked prior TB DNAm patterns to lymphoid leukemia, while dbGaP analysis identified associations with phenotypes like asthma, body mass index, tunica media, and lymphocyte count. Prior TB infection in PWH is associated with distinct DNAm changes in pathways related to neural function, cardiovascular health, and cancer risk, and is linked to more pronounced epigenetic age acceleration, suggesting epigenetic mechanisms for TB-related long-term complications.